Measuring human rights violations from an ecological perspective using a locally generated instrument: a cross-sectional study of Palestinians in the Israeli-occupied West Bank - Giacaman, Rita; Ghandour, Rula; Hammoudeh, Weeam (Frontiers in Public Health, 2025)
IntroductionThis study presents findings from a cross-sectional household survey conducted among Palestinians in the Israeli-occupied West Bank to assess the reported prevalence of human rights violations committed by various potential perpetrators.MethodsWe used a context-specific tool developed from the ground up using qualitative methods to enhance our understanding of what Palestinians consider to be human rights violations. This tool aligns with our conceptualization of potential perpetrators, which includes the family, the community, the Palestinian Authority, and the Israeli military occupier and colonizer of Palestinian land.ResultsOverall, as many as 60% of participants reported being exposed to one or more human rights violations, with the most frequently reported being restrictions on mobility, safety, freedom, and the exercise of political rights. Regression analysis revealed that women were more likely to report violations perpetrated by the family compared to men, whereas men were more likely to report violations by the Palestinian Authority and the Israeli military occupier. Palestinians living in Area C, fully controlled by Israel and where illegal Israeli settlements on confiscated Palestinian land are located, had higher odds of reporting experiences of general human rights violations, alongside those committed by the Israeli military occupier, the Palestinian Authority, and the family. Participants with lower educational levels and those from poorer backgrounds had higher odds of reporting human rights violations by all offenders.DiscussionThis study underscores the importance of considering the family and community as potential human rights perpetrators and highlights the significance of using mixed methods in research to ground findings in participant experiences. Particularly during wartime, as violence permeates daily life, the combination of violations from family, community, government, and military occupiers is likely to be synergistic, exacerbating the experienced suffering and making life increasingly difficult to endure. This may also lead to significant negative impacts on health, whether physical or mental, as health is fundamentally a social and political construct.